VISUAL OUTCOME AND COMPLICATIONS IN INTRA OCULAR FOREIGN BODIES: Intra Ocular Foreign Bodies - Khan, Nasrullah; Waheed, Khalid; Siddiq, Saqib; Tayyib, Muhammad (Pakistan Armed Forces Medical Journal, 2014)
Objective: To evaluate visual outcome and complications in intraocular foreign bodies.Study Design: Descriptive case series.Materials and Methods: This prospective study was carried out in the department of Ophthalmology, Services Hospital Lahore, over a period of one year from July 2008 to July 2009. Eighteen patients having magnetic or nonmagnetic intraocular foreign bodies (IOFBs) were included. The location of foreign body was determined with the help of slit lamp, direct and indirect ophthalmoscope, orbital radiogram, B-scan and CT scan. Patients with open entry wound underwent primary repair. Vitrectomy for intraocular foreign body was performed within two weeks of primary repair.Results: Eighteen eyes of 18 patients were analyzed. There were 17 (94.44%) males and 1 (5.66%) female. Preoperative visual acuity was perception of light in 9 (50%), hand movement in 5 (27.77%), finger counting in 2 (11.11%) and 6/60 in 2 (11.11%) patients. Post operative visual acuity was 6/18 or better in 6 (33.33%) and 6/60 in 4 (22.22%), hand movements in 6(33.33%), perception of light in 2 (11.11%) patients. Lens touch occurred in 1 (5.55%) patient and endophthalmitis developed in 1 (5.55%) patient. Giant retinal tear and total retinal detachment (RD) in 1 (5.55%) and phthisis bulbi in 1 (5.55%) patient.Conclusion: Intra ocular foreign bodies contribute a significant component of ocular morbidity associated with open globe injury. However with prompt treatment a useful vision can be restored.